2021
DOI: 10.3390/en14227787
|View full text |Cite
|
Sign up to set email alerts
|

Full-Scale Investigation of Dry Sorbent Injection for NOx Emission Control and Mercury Retention

Abstract: An innovative dry SNCR method realized by a sorbent injection applied to a stoker furnace is presented. The process is based on urea powder admixed with halloysite, an aluminosilicate clay mineral. Field tests were performed at an industrial stoker hot water boiler of 30 MWth capacity. A unique nozzle design for injecting powdery sorbents into the combustion zone was implemented. The base NOx emission without SNCR was determined to be 365 mg/Nm3. During the reference test, the emission was reduced to avg. 175 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Du et al [96] tested kaolin as an additive during highorganic solid waste pyrolysis and found its high adsorption capacity for Cd, Cr, Pb, Cr, Cu, Pb, and Zn. Wang et al [97] determined kaolin injection into the combustion zone to be an effective remedy to control submicron Pb emission over the temperature range from 850 • C to 900 • C and kaolin pre-mixed with the fuels as more effective at the temperature of 950 • C. A significant (over 10-times) mercury retention in fly ash was observed by Wejkowski et al [52] as a result of the injection of halloysite into the combustion zone of above 850 • C during the combustion of coal in a grate furnace. The metals' sorption ability could provide a solution for the problem of mercury release during the thermal conversion of waste and waste-derived fuels.…”
Section: Mitigation Of the Heavy Metals Emissionmentioning
confidence: 94%
See 1 more Smart Citation
“…Du et al [96] tested kaolin as an additive during highorganic solid waste pyrolysis and found its high adsorption capacity for Cd, Cr, Pb, Cr, Cu, Pb, and Zn. Wang et al [97] determined kaolin injection into the combustion zone to be an effective remedy to control submicron Pb emission over the temperature range from 850 • C to 900 • C and kaolin pre-mixed with the fuels as more effective at the temperature of 950 • C. A significant (over 10-times) mercury retention in fly ash was observed by Wejkowski et al [52] as a result of the injection of halloysite into the combustion zone of above 850 • C during the combustion of coal in a grate furnace. The metals' sorption ability could provide a solution for the problem of mercury release during the thermal conversion of waste and waste-derived fuels.…”
Section: Mitigation Of the Heavy Metals Emissionmentioning
confidence: 94%
“…Aluminosilicates can be considered excellent fuel additives since they meet all the specific requirements: they are characterized by high porosity and high specific surface, high reactivity, high melting points, and non-toxicity [50,51]. They are claimed to have no negative influence on the combustion process, which means they do not lower the combustion efficiency or favor the formation of any pollutants [52,53]. Their chemical stability and powdery structure make them easy to transport, store, and apply.…”
Section: Characteristics Of Aluminosilicate Clay Mineralsmentioning
confidence: 99%
“…If these problems appear, they can be minimized by using aluminosilicate fuel additives, such as halloysite, kaolin or bentonite. Their positive influence on plant-origin biomass and coal combustion has already been studied and successfully proven [55][56][57].…”
Section: Feedstock and Ash Characteristicsmentioning
confidence: 99%
“…The granular activated carbon, zeolites, and metal oxide sorbents reduced the mercury emission in exhausted gas by 90%, 87%, and 95.26%, respectively [20,21], as well as reduced the mercury in waste water by 81%, 99%, and 70-90%, respectively [22][23][24]. It is also possible to introduce sorbent directly into the boiler [25]. In recent years, there is a new material known as the sorbent polymer composite (SPC).…”
Section: Introductionmentioning
confidence: 99%